Cultivating Genuineness: Philosophy as a Way of Life in Li Zhi - Mina, Federico Daniel (2022)
Li Zhi (1527-1602) was one of the most controversial figures of his time. In his writings, we see a strong rebuke of some of the most important institutions of the society, and the quest for an open dialogue between the Three Teachings (sanjiao). In this paper I’m am going to show how some of his own life-choices and his ideas about how to live a genuine life are deeply intertwined. Also, how he contributed to China’s long tradition of recluses by proposing a novel way to understand how to live free from the coercion of society.